ASPEK SOSIAL EKONOMI DALAM ILEGAL LOGGING DAN DAMPAKNYA TERHADAP HUTAN TESSO-NILO, RIAU - Nurul Qomar (Jurnal Sagu, 2004)
Many problems have been faced by forestry based on social economic condition, special people who live aroundthe forest The objectives of this research arc to understand condition of social economic of the people livingaround the Tesso-Nilo forest who performed illegal logging activity and its impact to the Tesso-Nilo forest sub-system. Social economic data have been compiled with 3 methods: participative observation, in-depth interview,and secondary data. To know the Tesso-Nilo forest condition, secondary data were collected from 4 HPII's andal.so direct observation done by using quadrant plot The results of research .show that people who live aroundthe Tesso-Nilo forest considered forest as source of income by illegal logging activity. This was mainly causedby high growth of people due to swakarsa migration who were poor and "land-hanger". Ally, many of their oilpalm plantation failed, so they still continue performing illegal logging activity. Consequently, Tesso-Niloforest ecosystem has been degraded that will further threat elephant living in this forest.